Professor Claudine Blanchet-Bardon: French dermatologist and leading authority on inherited ichthyoses - A. Daunton, MBChB; A.R. Shipman, BMBCh (Wolters Kluwer, 2016)
This article recounts the early life and professional achievements through 2016 of Professor Claudine Blanchet-Bardon, a French dermatologist who is known for her work in dermatogenetics, genetic counseling, and the care of patients with ichthyoses among other important work.